Relationship Between Flexible Work Arrangements, Well-Being, and Performance of Employees During the COVID -19 Pandemic - Arora, Rupali; Pratibha, (Prabandhan: Indian Journal of Management, 2022)
The primary purpose of the present research paper was to investigate the influence of flexible work arrangements on personal and family well-being and performance of employees. The study also examined the moderating role of managerial support on the relationship between flexible work arrangements and well-being & performance. The target respondents were the teleworkers employed with Indian IT organizations located in North India. Data were gathered from 412 teleworkers to study the hypotheses, and Smart PLS 2.0 was employed to analyze the data. The results revealed a significant relationship between flexible work arrangements, personal and family well-being, and employee performance. The study further confirmed the significant and moderating effect of managerial support on the relationship between flexible work arrangements and performance. During the work-from-home policies at the workplace, the employees perceived that receiving support from the managers helped them perform well. As the COVID-19 pandemic has affected the economies globally, the present study’s findings would be essential for the managers to support their employees during such crises.